The dark side of bright traits: How context cues misdirect facets of conscientiousness - Jeong, Sophia Soyoung; Korsgaard, M. Audrey; Morrell, Daniel (Personnel review, 2021)
PurposeThe authors test the proposition that there are dark sides to conscientiousness that are revealed when examining lower-level facets. The authors propose that potentially dysfunctional behavior is triggered by context cues that are relevant to duty versus achievement striving.Design/methodology/approachThe authors conducted two laboratory experiments designed to test how context cues that are specific to duty and achievement striving influence the relationship between these facets and quality versus quantity dimensions of task performance.FindingsIn Study 1, the authors found that normative quality cues led to a stronger relationship between duty and discretionary quality performance. In Study 2, achievement striving was associated with lower levels of quality performance in the presence of competitive feedback cues.Research limitations/implicationsThe findings illustrate that the dark side of duty and achievement striving emerges in two ways. First, when there is normative pressure for quality, dutiful individuals are apt to sacrifice efficiency. Second, when there is competitive feedback, achievement striving individuals focus on performance standards at the detriment of quality.Practical implicationsThe findings point to the importance of precision and specificity when using personality measures for staffing. Equally important is the informational content of cues conveyed by the social, task and organizational context, in leveraging the impact of personality in the workplace.Originality/valueThis paper clarifies the dark side and bright side contradiction of conscientiousness, adding to the growing literature on unique and often competing consequences of duty and achievement striving. The authors also draw attention to the importance of the content of contextual cues, in trait activation of personality.